Synthesis and Characterization of Reduced Graphene Oxide from Nipah Shell Charcoal (Nypa fruticans Wurmb) using Microwave Irradiation - Ilma Fadlilah; Ayu Pramita; Rosita Dwityaningsih (Jurnal Kimia Sains dan Aplikasi, 2024)
Graphene, an allotrope of carbon, consists of a single layer of carbon atoms arranged in a honeycomb lattice and holds significant potential for diverse applications. This study focuses on the synthesis of reduced graphene oxide (rGO) from nipah shell charcoal (Nypa fruticans Wurmb) using a modified Hummer’s method combined with microwave irradiation, employing L-ascorbic acid as the reducing agent. The synthesized rGO was characterized using Fourier Transform Infrared (FTIR) spectroscopy, X-ray Diffraction (XRD), and Scanning Electron Microscopy coupled with Energy Dispersive X-ray analysis (SEM-EDX). The FTIR spectra revealed an aromatic C=C ring stretching vibration at 1591.47 cm-1. The XRD analysis showed characteristic rGO peaks at 2θ ~ 27.58° and 48.45°. SEM images indicated that the rGO exhibited sheet-like structures with slight wrinkling. Elemental analysis identified carbon and oxygen as the primary elements in both GO and rGO, alongside trace impurities, including N, Mg, Al, Si, Ca, Zn, and S. An increase in the C/O ratio from 1.90 in GO to 2.38 in rGO confirmed the successful synthesis of reduced graphene oxide.